Surgical experience of extracorporeal membrane oxygenation for neonates with severe respiratory failure - Qi-Liang Zhang; Xiu-Hua Chen; Si-Jia Zhou; Hua Cao; Qiang Chen (BMC Surgery, 2023)
Abstract Objective Extracorporeal membrane oxygenation (ECMO) has been increasingly used for severe neonatal respiratory failure refractory to conventional treatments. This paper summarizes our operation experience of neonatal ECMO via cannulation of the internal jugular vein and carotid artery. Methods The clinical data of 12 neonates with severe respiratory failure who underwent ECMO via the internal jugular vein and carotid artery in our hospital from January 2021 to October 2022 were collected. Results All neonates were successfully operated on. The size of arterial intubation was 8 F, and the size of venous intubation was 10 F. The operation time was 29 (22–40) minutes. ECMO was successfully removed in 8 neonates. Surgeons successfully reconstructed the internal jugular vein and carotid artery of these neonates. Arterial blood flow was unobstructed in 5 patients, mild stenosis was present in 2 patients, and moderate stenosis was present in 1 patient. Venous blood flow was unobstructed in 6 patients, mild stenosis was present in 1 patient, and moderate stenosis was present in 1 patient. The complications were as follows: 1 case had poor neck incision healing after ECMO removal. No complications, such as incisional bleeding, incisional infection, catheter-related blood infection, cannulation accidentally pulling away, vascular laceration, thrombosis, cerebral haemorrhage, cerebral infarction, or haemolysis, occurred in any of the patients. Conclusion Cannulation of the internal jugular vein and carotid artery can quickly establish effective ECMO access for neonates with severe respiratory failure. Careful, skilled and delicate operation was essential. In addition, during the cannulation process, we should pay special attention to the position of cannulation, firm fixation and strict aseptic operation.